Acceleration and Cultural Change Dialogues from an Overheated World - Eriksen, Thomas Hylland; Visentin, Martina (SpringerBriefs in Anthropology,, 2024)
This open access book includes socio-anthropological and anthropo-sociological conversations between one of the world's leading anthropologists, Thomas Hyland Eriksen, and a young scholar, using his groundbreaking "overheating" approach.This book includes socio-anthropological and anthropo-sociological conversations between one of the world's leading anthropologists, Thomas Hyland Eriksen, and a young scholar, using his groundbreaking "overheating" approach. From the pandemic to the spread of nationalism, from the Anthropocene to the Homogenocene, the authors discuss the most urgent issues of current society: e.g., the loss of biological and cultural diversity owing to the forces of globalisation; and the emergence of new forms of diversity through globalisation and migration; the intersectional dimension of climate change; the incredible rising of anger demonstrations around the world and resentful, overheated identities often linked to right-wing nationalism;the way digital devices have changed the meaning of temporality in people's life-worlds; the regulatory and competitive pressures on universities which are a result of many factors in the intersection of globalisation, massification and marketisation; youth's weakened belief in progress connected to changes in the contemporary world, such as growing inequality, political alienation and environmental destruction; recent pathbreaking research and original theory in sociology and anthropology related to the changes in an overheated world; and what post-Coronavirus social life might become. Highly topical, engaging and written in a conversational style, this book is a must-read for social scientists and discerning lay persons who want a fresh perspective on understanding the critical issues of our time. .